Clinical Spectrum and Radiological Evaluation of Urinary Tract Infections in Children - Irshad Ahmad, Abdul Basit Niazi, Jaweria Razzaque, Muhammad Ikram, Misbah Munir, Wajeeha Imran Andrabi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate clinical spectrum and radiological findings in pediatric patients presenting with urinary tract infection. Study Design: Cross sectional study Place and Duration of Study: Radiology and Pediatric Departments, Niazi Medical & Dental College, Niazi Welfare Teaching Hospital Sargodha from 1st January 2023 to 31st July 2023. Methodology: One hundred and fourteen children were enrolled. Urine samples of patients under three months of age were collected by suprapubic aspiration, while in the older children urine was collected by clean catch method or via catheter in catheterized children. All children and neonates having urine routine examination proven urinary tract infections were enrolled in the study. The radiological investigations included ultrasound of the renal tract, intravenous pyelography and micturating cystourethrogram. Clinical signs and symptoms of urinary tract infections, radiological findings, and the history of recurrent urinary tract infections, as well as any complications arising from this infection, were documented using separate questionnaires. Results: There were 52.6% males and 47.4% females. Fever was a prevalent clinical symptom, observed in 57.0% of cases, while vomiting was documented in 16.7% of patients. Failure to thrive was reported in a minority of cases (12.3%), while abdominal pain was relatively common (31.6%). Edema, dysuria, hematuria, urinary urgency, urinary incontinence, and urinary retention were generally rare symptoms in this population. Conclusion: The diagnosis and management of pediatric urinary tract infections, underscoring the importance of early detection, individualized treatment, and evidence-based guidelines. It contributes valuable insights to the field, while also recognizing the need for further research to enhance our understanding of this prevalent pediatric condition. Keywords: Urinary tract infection, pediatric population, ultrasound, IVU, MCUG